2010
DOI: 10.1111/j.1365-2648.2010.05428.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of perineal trauma on postpartum sexual function

Abstract: Limiting perineal trauma during delivery is important for the resumption of sexual intercourse after childbirth. Routine episiotomy and fundal pressure should be avoided to prevent perineal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0
11

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 20 publications
2
60
0
11
Order By: Relevance
“…During the vaginal delivery, the most important risk factor for sexual dysfunction is perineal stretching and trauma [27]. The majority of patients in the study and control groups had a history of giving birth by cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…During the vaginal delivery, the most important risk factor for sexual dysfunction is perineal stretching and trauma [27]. The majority of patients in the study and control groups had a history of giving birth by cesarean section.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that primiparity has a negative impact on subsequent sexual function [12,39,40]. This could be related to birth difficulty especially the degree of vaginal tear [41].…”
Section: Resumption Of Sexual Activity Postpartummentioning
confidence: 99%
“…Być może dlatego pierwsze zbliżenie po porodzie porównywane jest przez niektóre kobiety do inicjacji seksualnej. Wiadomo natomiast, że nieudane relacje intymne w tym okresie mogą inicjować u kobiet dysfunkcje seksualne [14,15].…”
Section: Dyskusjaunclassified